Post Hoc Analysis of the Phase II/III APRIL‐SLE Study: Association Between Response to Atacicept and Serum Biomarkers Including BLyS and APRIL. Issue 1 (2nd December 2016) - Gordon, Caroline; Wofsy, David; Wax, Stephen; Li, Yong; Pena Rossi, Claudia; Isenberg, David
Abstract : Objective: To assess the relationship between treatment response, baseline biomarker levels, and atacicept exposure in patients with systemic lupus erythematosus (SLE) in the phase II/III APRIL‐SLE study. Methods: We performed a post hoc analysis of patients who received placebo, atacicept 75 mg, or atacicept 150 mg in a randomized, controlled, 52‐week trial. Serum levels of BlyS and APRIL were measured at baseline, and serum levels of Ig and the numbers of naive B cells and plasma cells were measured at baseline and during treatment. Atacicept exposure was determined by assessment of the serum trough concentrations throughout the 52‐week trial period. Associations between these parameters, treatment response (reduction in British Isles Lupus Assessment Group A or B flare), and infection rates were explored. Results: Recurrent high baseline levels of both BLyS (≥1.6 ng/ml) and APRIL (≥2.2 ng/ml) correlated with a greater treatment response (flare rate 75.7% with placebo, and 50.0% and 32.0% with atacicept 75 mg and atacicept 150 mg, respectively) compared with lower baseline levels of both. Increased atacicept exposure correlated with reduced flare rates (60.5% with placebo; 63.4%, 61.0%, 48.8%, and 29.3% in the 4 quartiles, from lowest to highest atacicept exposure). Greater pharmacodynamic responses (reduced Ig levels and naive B cell and plasma cell numbers) were associated with greater reductions in the flare rate. Infection rates were similar regardless of biomarker levels at baseline or at the time of atacicept exposure. Conclusion: These post hoc analyses demonstrate a dose‐response relationship between atacicept concentrations, reduced Ig levels, and reduced flare rates and suggest that baseline biomarkers such as elevated serum levels of BLyS and APRIL may help to identify the patients who are most likely to benefit from atacicept treatment.